Analisis Pemaafan Hakim Ditinjau dari Ringannya Perbuatan Yang Dilakukan Oleh Anak - Syahputra, Annisa Nur Fadillah; Setyorini, Erny Herlin (Law and Humanity, 2024)
Article 70 of Law Number 11 Year 2012 regulates the forgiveness of judges, but in the Explanation section, there is no more detailed provisions regarding the explanation of the article, especially on the meaning of the article. More detailed provisions regarding the explanation of the article, especially on the meaning of “the severity of the act”, thus creating legal uncertainty. The method in this writing is normative legal research with a statutory approach and Conceptual Approach. The purpose of the research is to understand and analyze what is meant by the severity of the act as the basis for the judge's consideration in giving an excuse decision. The results showed that by considering the criminal punishment against child offenders, then Article 70 of the SPPA Law, especially the phrase “the lightness of the act”, can be interpreted as a minor criminal offense.